Vertical gradients in species richness and community composition across the twilight zone in the North Pacific Subtropical Gyre - Sommer, Stephanie A. (2017)
Although metazoan animals in the mesopelagic zone play critical roles in deep pelagic food webs and in the attenuation of carbon in midwaters, the diversity of these assemblages is not fully known. A metabarcoding survey of mesozooplankton diversity across the epipelagic, mesopelagic and upper bathypelagic zones (0–1500 m) in the North Pacific Subtropical Gyre revealed far higher estimates of species richness than expected given prior morphology-based studies in the region (4,024 OTUs, 10-fold increase), despite conservative bioinformatic processing. Operational taxonomic unit (OTU) richness of the full assemblage peaked at lower epipelagic–upper mesopelagic depths (100–300 m), with slight shoaling of maximal richness at night due to diel vertical migration, in contrast to expectations of a deep mesopelagic diversity maximum as reported for several plankton groups in early systematic and zoogeographic studies. Four distinct depth-stratified species assemblages were identified, with faunal transitions occurring at 100 m, 300 m and 500 m. Highest diversity occurred in the smallest zooplankton size fractions (0.2–0.5 mm), which had significantly lower % OTUs classified due to poor representation in reference databases, suggesting a deep reservoir of poorly understood diversity in the smallest metazoan animals. A diverse meroplankton assemblage also was detected (350 OTUs), including larvae of both shallow and deep living benthic species. Our results provide some of the first insights into the hidden diversity present in zooplankton assemblages in midwaters, and a molecular reappraisal of vertical gradients in species richness, depth distributions and community composition for the full zooplankton assemblage across the epipelagic, mesopelagic and upper bathypelagic zones.